Prolactin-releasing peptide: a new tool for obesity treatment - Kuneš, Jaroslav; Pražienková, Veronika; Popelová, Andrea; Mikulášková, Barbora; Zemenová, Jana; Maletínská, Lenka (The Journal of endocrinology, 2016)
Obesity is an escalating epidemic, but an effective noninvasive therapy is still scarce. For obesity treatment, anorexigenic neuropeptides are promising tools, but their delivery from the periphery to the brain is complicated because peptides have a low stability and limited ability to cross the blood-brain barrier. In this review, we summarize results of several studies with our newly designed lipidized analogs of prolactin-releasing peptide (PrRP). PrRP is involved in feeding and energy balance regulation as demonstrated by obesity phenotypes of both PrRP- and PrRP-receptor-knockout mice. Lipidized PrRP analogs showed binding affinity and signaling in PrRP receptor-expressing cells similar to natural PrRP. Moreover, these analogs showed high binding affinity also to anorexigenic neuropeptide FF (NPFF)-2 receptor. Acute peripheral administration of myristoylated and palmitoylated PrRP analogs to mice and rats induced strong and long-lasting anorexigenic effects and neuronal activation in the brain areas involved in food intake regulation. Two-week-long subcutaneous administration of palmitoylated PrRP31 and myristoylated PrRP20 lowered food intake, body weight, improved metabolic parameters and attenuated lipogenesis in mice with diet-induced obesity. A strong anorexigenic, body weight-reducing and glucose tolerance-improving effect of palmitoylated-PrRP31 was shown also in diet-induced obese rats after its repeated 2-week-long peripheral administration. Thus, the strong anorexigenic and body weight-reducing effects of palmitoylated PrRP31 and myristoylated PrRP20 make these analogs attractive candidates for antiobesity treatment. Moreover, PrRP receptor might be a new target for obesity therapy.
Keywords: Prolactin-Releasing Hormone; Appetite Regulation; lipidization; Obesity; obesity; anorexigenic; lékové transportní systémy; hormon uvolňující prolaktin; Anti-Obesity Agents; zvířata; Humans; mice; prolactin-releasing peptide; regulace chuti k jídlu; obezita; Drug Delivery Systems; látky proti obezitě; lidé; GPR10; Animals